THE ROLE OF TECHNOLOGY IN TEACHING ENGLISH AS A FOREIGN LANGUAGE IN UZBEKISTAN - Umarjonova Azizaxon Nuriddin qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
In the modern world, technology plays an important role in education, especially in teaching English as a foreign language. In Uzbekistan, the use of digital tools, online platforms, multimedia resources, and mobile applications has significantly changed the way English is taught and learned. Technology helps teachers create more interactive lessons, improve students’ motivation, and develop all language skills such as listening, speaking, reading, and writing. This article discusses the role of technology in teaching English in Uzbekistan, its advantages, challenges, and its impact on students’ language learning process. The article also explains how technology can improve teaching methods and create a more effective learning environment for English language learners. This article examines the role of technology in teaching English as a foreign language in Uzbekistan. It highlights how digital tools, online platforms, and multimedia resources have transformed traditional teaching methods into more interactive and student-centered approaches. The study discusses the advantages of technology, such as increased student motivation, access to authentic materials, and opportunities for independent learning. At the same time, it addresses challenges including limited technological resources, insufficient digital skills, and potential distractions. The article concludes that despite these challenges, technology significantly enhances the effectiveness of English language teaching and will continue to play a crucial role in the future of education in Uzbekistan.